Optimization of Therapy for Relapse of Bipolar Affective Disorders against the Background of Covid-19 (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The clinical features of bipolar affective disorder are characterized by long-term dynamics that begin gradually in the form of phobic neurosis with panic attacks, followed by an increase in affective symptoms with the transition of symptoms to the level of general anxiety disorder and the spread of depressive symptoms against the background of Asthenic Syndrome with vegetative insufficiency due to complications or coronavirus infection.